Safety and toxicological evaluation of Meratrim®: An herbal formulation for weight management. (April 2015) - Saiyed, Zainulabedin M.; Sengupta, Krishanu; Krishnaraju, Alluri V.; Trimurtulu, Golakoti; Lau, Francis C.; Lugo, James P.
Highlights: Meratrim is an herbal formulation for weight management. Safety of Meratrim was assessed in a battery of in vitro and in vivo toxicity studies. Genotoxicity studies showed that Meratrim is non-mutagenic. Acute oral LD50 of Meratrim was determined to be >5000 mg/kg in rats. NOAEL for Meratrim was determined to be 1000 mg/kg/day in rats. Abstract: Meratrim is a unique dietary ingredient consisting of extracts from Sphaeranthus indicus flower heads and Garcinia mangostana fruit rind. Clinical studies have demonstrated that Meratrim is effective and well-tolerated in weight management. Herein we assessed the broad spectrum safety of Meratrim in a battery of in vitro and animal toxicological studies including a sub-chronic repeated-dose 13-week oral toxicity study to determine the no-observable-adverse-effect-level (NOAEL). The LD50 levels of Meratrim in Sprague-Dawley (SD) rats, as determined by the acute oral and dermal toxicity studies, were >5000 and >2000 mg/kg body weight, respectively. The primary skin and eye irritation tests classified Meratrim as non-irritating to the skin and mildly irritating to the eye. Genotoxicity studies showed that Meratrim is non-mutagenic. In the repeated-dose 13-week oral toxicity study, SD rats were orally gavaged with Meratrim at 0, 250, 500 or 1000 mg/kg/day. No morbidity, mortality, or significant adverse events were observed either during the course of the study or on the 13th week. The NOAEL of Meratrim was concluded to be 1000 mg/kg of body weight/day in male and female SD rats. These results, combined with the tolerability of Meratrim in the human clinical trials, demonstrate the broad spectrum safety of Meratrim.